JOURNAL OF GOVERNMENT & POLITICS : The Politics of Technocracy in Malaysia (1957-2012) - Jason Seong Wei Loh (FISIPOL UMY, 2016)
Malaysia's technocracy (administrative elite) and the government of the day (political elite) have had and continue to enjoy a harmonius and symbiotic relationship.